Hybrid tabu search algorithm for weight optimization of planar steel frames. Issue 8 (3rd August 2021) - Tayfur, Bilal; Yilmaz, Hamid; Daloğlu, Ayşe T.
Abstract : In this study, a hybrid metaheuristic algorithm called Hybrid Tabu Search (HTS) is proposed for the weight optimization of planar steel structures. The effectiveness of HTS lies in improving the initial conditions of a tabu search algorithm with a greedy search algorithm and a swap operator used in the phase of section selection. The effectiveness of the proposed method is tested and validated on three different benchmark examples. C♯ software is developed to perform the structural analyses. Numerical results obtained by using HTS showed that the proposed method achieved significantly lighter frame weights in most of the benchmark examples. When the method was examined in terms of computational efficiency, HTS was at a level that can compete with other algorithms examined within this study, although it did not provide a significant advantage.